MENINGKATKAN KECERDASAN KINESTETIK MELALUI TARIAN TRADISIONAL DI RA FIRDAUS GRIYA PRIMA - Claury Oktavia; Masganti Sit; Muhammad Basri (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2022)
An abstranct is a brief summary of a research article, thesis, review, conference proceeding or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry for any given academic paper or patent application. Absatrcting and indexing services for various academic discipline are aimed at compiling a body of literature for that particular subject. Abstract length varies by discipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper. One of the most important intelligences for children's development is kinesthetic intelligence. Kinesthetic intelligence is intelligence related to the processing of human body movements. Based on this, this study aims to improve kinesthetic intelligence by providing actions in the form of traditional Kuala Deli dance for 12 children aged 5-6 years at RA Firdausy Griya Prima. This study uses a type of classroom action research in which researchers go directly to provide action to children. Data analysis in this study used qualitative analysis in the form of a description of the results of the assessment and quantitative in the form of a percentage increase from the results of the actions taken. Collecting data in this study using observation techniques that are supported by child assessment observation sheets. This research carried out the action up to two cycles. The results of this study indicate that the pre-cycle percentage of children's kinesthetic intelligence only reached 16.6%, in cycle 1 it reached a value of 41.6%, and in cycle 3 it got a percentage of 83.3%. These results indicate that kinesthetic intelligence can be improved through traditional dance learning activities.